Sosialisasi Pencegahan Stunting di Desa Bandur Picak, Kecamatan Koto Kampar Hulu - Charlina Charlina; Silvya Sischa Yulia Putri; Muhammad Arief Fadilah; Salsabila Filjania Ijjati; Ghina Ans Afsya; Dina Savira; Anggie Andika Putri; Almira Azalia Natasya Putri; Nofriandi Ramadhan; Muhammad Naufal Ali Akbar Nasution; Mohammad Zascka Ziansyah (Fakultas Ilmu Budaya Universitas Lancang Kuning, 2022)
Stunting is a health problem that is often found in developing countries, including Indonesia. The prevalence of stunting in Indonesia is the fifth largest in the world. Stunting is a linear growth disorder caused by chronic malnutrition. People who live in the outlying areas receive less attention from the local health office so the stunting sufferers have not received a proper treatment. Currently, Indonesia has entered a new normal era where community activities run as usual, whether it’s the center of government, educational institutions, health agencies and others. This is the background for us to hold a stunting socialization program, especially in Bandur PicakVillage, Koto Kampar Hulu District. This article aims to provide information related to stunting socialization and stunting prevention interventions for pregnant women about nutrition during pregnancy in an effort to prevent stunting. This socialization is quite effective in providing information on how to prevent and reduce the incidence of stunting in children through pregnant women. With the socialization of stunting in Bandur Picak Village, this socialization can increase public awareness regarding child growth and development , so hoped that it can prevent stunting and reduce the percentage of stunting in Indonesia, especially in Bandur Picak Village, Koto Kampar Hulu District, Kampar Regency, Riau Province. Keywords : Stunting, Educational, Health Agencies